2014
DOI: 10.7567/apex.7.045501
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cu2O/γ-FeOOH heterojunction solar cells using electrodeposition

Abstract: Cu 2 O/γ-FeOOH heterojunction solar cells were fabricated using galvanostatic-potentiostatic electrodeposition methods. The γ-FeOOH films showed n-type conductivity with a band gap of 2.2 eV. The electrodeposited Cu 2 O/γ-FeOOH heterojunction exhibited photovoltaic characteristics with a short-circuit current density of 0.95 mA/cm 2 and open-circuit voltage of 0.11 V. Using core-level spectroscopy, it was demonstrated that the Cu 2 O/FeOOH heterostructure exhibited a type II junction with a valence band offset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In Figure S5 (Supporting Information), the peak of Cu2p 3/2 for PhCCCu/Cu 2 O photocathode is fitted to two peaks with binding energies of 935.8 and 933.4 eV, respectively. [22,23] The main peak at 933.4 eV is attributed to Cu + , while the small peak at 935.8 eV is assigned to Cu 2+ , again confirming the trace existence of CuO in the prepared PhCCCu/Cu 2 O photocathode. In Figure S6 (Supporting Information), the peak at 531.6 eV for O1s mainly belongs to the signal of Cu-O in Cu 2 O.…”
Section: Characterizationssupporting
confidence: 53%
See 1 more Smart Citation
“…In Figure S5 (Supporting Information), the peak of Cu2p 3/2 for PhCCCu/Cu 2 O photocathode is fitted to two peaks with binding energies of 935.8 and 933.4 eV, respectively. [22,23] The main peak at 933.4 eV is attributed to Cu + , while the small peak at 935.8 eV is assigned to Cu 2+ , again confirming the trace existence of CuO in the prepared PhCCCu/Cu 2 O photocathode. In Figure S6 (Supporting Information), the peak at 531.6 eV for O1s mainly belongs to the signal of Cu-O in Cu 2 O.…”
Section: Characterizationssupporting
confidence: 53%
“…[16,17] However, this method is not suitable for large-scale production because of the cumbersome processes and expensive equipment. Consequently, the stability of the composite Cu 2 O photocathodes were also improved by combining with g-C 3 N 4 , [18][19][20] NiS, [21] FeOOH, [22,23] Cu 2 S, [24][25][26] and MOFs [27,28] to form junctions through diverse methods, such as drop coating, alternate adsorption assembly and electrodeposition. For further improving the photostability of Cu 2 O photocathode, some more effective protective layer materials need to be developed via repeatable processes and technologies.It has been reported that cutting off the reactions between photoelectrodes and electrolyte solution can effectively resist its photocorrosion.…”
mentioning
confidence: 99%
“…As-synthesized β-FeOOH was initially used in the experiment, which requires 1.2 eV for oxygen and hydrogen to undergo redox reactions . However, the experiment was unsuccessful due to the insufficient energy exhibited by β-FeOOH. , Thus, β-FeOOH could only be used as a buffer layer to absorb visible light during electrolysis by integrating electrochemical fields. , In this case, an applied voltage is required and visible light is irradiated on a thin film . However, although FeOOH absorbs visible light, the energy of visible light is insufficient to generate hydrogen; hence, FeOOH cannot function as a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Thus, β-FeOOH could only be used as a buffer layer to absorb visible light during electrolysis by integrating electrochemical fields. 16,17 In this case, an applied voltage is required and visible light is irradiated on a thin film. 18 However, although FeOOH absorbs visible light, the energy of visible light is insufficient to generate hydrogen; hence, FeOOH cannot function as a photocatalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has also been utilized for the fabrication of heterojunction structures for solar cells. 26,27) In particular, the pulse electrodeposition method produces denser and smoother SnS thin film compared to direct-current (DC) electrodeposition having a onestep potential. 16) As evidenced in the PEC experiment, the pulse electrodeposited SnS exhibited a threefold increase in photocurrent compared to DC electrodeposited SnS (Fig.…”
mentioning
confidence: 99%